Self-repairing high-toughness ionic conductive elastomer and preparation method thereof

By adopting soft and hard phase collaborative strategies and dynamic bond design in flexible ion conductive materials, the lack of materials in mechanical strength, toughness and self-repair ability is solved, and high-performance, safe and reliable self-repairable ion conductive elastomer is achieved. .

CN119463101APending Publication Date: 2025-02-18BLUE OCEAN & BLACK STONE TECH CO LTD (FUJIAN)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411685639.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-23
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing flexible ionic conductive materials have poor performance in terms of mechanical strength and toughness, which has hidden dangers of leakage of fluids, and are difficult to repair themselves after repeated wear or rupture.

Method used

Using thermoplastic polyurethane-based ionic conductive elastomer, prepared by soft-hard-phase synergistic strategy, dynamic disulfide bonds and hexafluor hydrogen bonds are introduced to achieve self-healing performance, and ionic conductivity is improved through loose Li+-O coordination soft phase .

Benefits of technology

It achieves excellent mechanical properties, fast self-healing performance at room temperature and high ionic conductivity, avoids safety hazards of liquid leakage, and improves the use stability and reusability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463101A_ABST
    Figure CN119463101A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of flexible ionic conductive materials, in particular to a self-repairing high-toughness ionic conductive elastomer and a preparation method thereof. The preparation method comprises the following steps: S1, drying a diisocyanate monomer; s2, treating a polyether glycol monomer; s3, preparation of a prepolymer; s4, adding a chain extender; s5, curing a reaction product; s6, introduction of a lithium salt: introducing ionic conductivity by co-dissolving the elastomer and the dried lithium salt, and maintaining the reversibility and self-healing ability of the material at the same time; and S7, final curing is conducted, specifically, curing is conducted again in the modes of pouring and solvent removing, and the final ionic conductive elastomer is formed. The invention provides a method based on a soft and hard phase synergistic effect in a polymer network. Through the synergistic effect of the steps, the ionic conductive elastomer which can be self-repaired, has ultrahigh mechanical strength, ultrahigh stretchability, super-tough mechanical property and excellent ionic conductivity and can be repeatedly used is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of flexible ion conductive materials, and in particular to a self-repairing, high-toughness ion conductive elastomer and a preparation method thereof. Background Art

[0002] The rapid development of flexible electronic technology, including electronic skin, flexible robots, wearable health detection, stretchable light-emitting displays and soft sensors, has triggered a growing demand for flexible conductive materials. Flexible conductive materials can be divided into electronic conductors and ionic conductors, distinguished by their different conductive principles. Traditional conductive elastomers are usually used in combination with carbon-based nanomaterials, conductive polymers or technologies. Most of them have poor stretchability, poor transparency, unreliable electron transfer paths, and are prone to separation of substrate materials from conductive fillers under large deformations, resulting in degradation of conductive functions. In contrast, flexible and stretchable ionic conductors can adapt to a wide range of deformations and repeated stretching. Therefore, flexible and stretchable ionic conductor materials are indispensable substrates in the development of flexible electronic devices.

[0003] At present, the most widely studied flexible ion conductive materials include hydrogels, ion gels and organogels, which are widely reported to be used to make flexible and stretchable ion conductive elastomers. However, the polymer network of such gel-state ion conductive elastomers usually contains a large amount of liquid, and there are problems such as water leakage, liquid leakage, and safety hazards in actual applications, which are specifically manifested in poor thermal stability and low operating voltage. In addition, due to the presence of liquid, its mechanical properties are poor, which further hinders its application in actual production and life. In addition, most ion conductive elastomers often undergo accidental physical damage such as repeated wear, scratches or ruptures during use, resulting in performance failure, which seriously affects the actual application effect of the conductive material. Therefore, it is of great significance to develop an ion conductive elastomer that is liquid-free, safe and reliable, self-repairable, and highly tough. Summary of the invention

[0004] In response to the problems of poor mechanical strength and toughness, leakage safety hazards and poor reversibility of material structure of traditional ion conductive elastomers, this application designs an ion conductive elastomer based on thermoplastic polyurethane, provides a self-repairing and highly tough ion conductive elastomer and its preparation method, and the ion conductive elastomer prepared by the strategy of soft and hard phase synergy has excellent mechanical properties, fast self-healing properties at room temperature and high ionic conductivity. These properties are currently at the leading level among ion conductive elastomers.

[0005] In the first aspect, the present application provides a method for preparing a self-repairing high-toughness ion-conductive elastomer, using the following technical solution: A method for preparing a self-repairing high-toughness ion-conductive elastomer comprises the following steps: S1. Take the diisocyanate monomer and dry it in a vacuum oven at 60-100°C to remove water for at least 12 hours; S2, adding polyether diol monomer into the bottle, stirring the polyether diol monomer at 80-120° C., cyclically evacuating and filling with protective gas for at least 3 times, then maintaining the evacuation state for at least 2 hours, cooling to 60-70° C., and finally filling with protective gas; wherein the protective gas used is nitrogen or other inert gas; S3, dissolving the diisocyanate monomer treated in step S1 in an anhydrous solvent with a mass ratio of 1:10 to 10:1 at a molar ratio of diisocyanate monomer to polyether diol monomer of 2:1, adding the polyether diol monomer dried in step S2 after ultrasonic dissolution for at least 30 minutes, and then adding 10 to 30 μL of a catalyst, stirring and reacting at 60 to 80° C. for at least 30 minutes to obtain a prepolymer product; S4, dissolving a chain extender containing a reversible bond in an anhydrous solvent with a mass ratio of 1:10 to 10:1 to obtain a chain extender solution, wherein the anhydrous solvent is the same as the anhydrous solvent in step S3; S5, further cooling the prepolymer product in step S3 to 30-60°C, then adding the chain extender solution, and stirring the reaction for at least 12 hours; S6, pouring the reaction product in step S5 into a polytetrafluoroethylene mold, and removing a large amount of solvent in a 60-70° C. forced air oven for at least 12 hours, and then transferring to a 60-70° C. vacuum oven to remove residual solvent, to obtain a self-repairing high-toughness elastomer; S7, dissolving the self-healing high-toughness elastomer in step S6 and 10-40% by mass of dry lithium salt in an anhydrous solvent with a mass ratio of 1:10 to 10:1, and stirring for at least 12 hours to obtain a uniform solution; S8. Pour the uniform solution in step S7 into a polytetrafluoroethylene mold, remove a large amount of solvent in a 60-70°C forced air oven for at least 12 hours, and then transfer to a 60-70°C vacuum oven to remove residual solvent to obtain a self-repairing and highly tough ion conductive elastomer.

[0006] By adopting the above technical scheme, the present application provides a method based on the synergistic effect of soft and hard phases in the polymer network, and the following steps are synergistically prepared to produce an ion conductive elastomer that can repair itself, has ultra-high mechanical strength, ultra-strong stretchability, ultra-tough mechanical properties, excellent ionic conductivity and can be reused: 1. Drying of diisocyanate monomer: Drying and removing water in a vacuum oven for at least 12 hours to ensure that the anhydrous reaction conditions are met in the subsequent reaction and avoid side reactions. 2. Treatment of polyether diol monomer: Cyclic vacuuming and filling with protective gas at a specific temperature to ensure that the polyether diol monomer reacts in an oxygen-free environment while maintaining its activity. 3. Preparation of prepolymer: Through the molar ratio reaction of diisocyanate monomer and polyether diol monomer, adding a catalyst, reacting at a specific temperature to generate a prepolymer, which is a key step in constructing the basic structure of the ion conductive elastomer. 4. Adding a chain extender: The addition of a chain extender is to introduce a reversible bond to provide a basis for subsequent self-healing properties. 5. Curing of the reaction product: The reaction product is poured into a mold and cured by removing the solvent to form a preliminary elastomer structure. 6. Introduction of lithium salt: by dissolving the elastomer with dry lithium salt, ion conductivity is introduced while maintaining the reversibility and self-healing ability of the material. 7. Final curing: curing again by pouring and removing the solvent to form the final ion conductive elastomer. In summary, the key to this application is to adopt a soft and hard phase synergy strategy, that is, through loose Li + The -O coordinated soft phase realizes fast and uniform lithium ion transmission, while the dynamic disulfide bonds and hexavalent hydrogen bonds in the hard phase are broken and reorganized, which enables the elastomer to have self-healing ability and excellent mechanical properties at room temperature. This synergistic effect not only improves the ionic conductivity of the material, but also enhances its mechanical properties and self-healing ability, making the final product highly tough and reusable, while avoiding safety hazards such as leakage. In addition, the entire preparation process is simple, low-cost, and suitable for commercial production.

[0007] Preferably, in step S1, the diisocyanate monomer includes one or more of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, butyl diisocyanate, alicyclic diisocyanate and 4,4'-dicyclohexylmethane diisocyanate.

[0008] Preferably, in step S2, the polyether diol monomer includes one or more of polypropylene glycol, polyethylene glycol, polytetramethylene glycol, polycaprolactone glycol and polytrimethylpropylene glycol.

[0009] Preferably, in step S3, the anhydrous solvent includes one of N,N-dimethylformamide and N,N-dimethylacetamide; and the catalyst is one of diisobutyltin dilaurate and triethanolamine.

[0010] Preferably, in step S4, the chain extender is composed of 4,4'-diaminodiphenyl disulfide and succinic acid dihydrazide in a molar ratio of 10:1 to 1:10.

[0011] Preferably, in step S5, the method of adding the chain extender solution is to add it dropwise and slowly using a constant pressure separatory funnel.

[0012] Preferably, in step S6, the method of pouring the reaction product into the polytetrafluoroethylene mold is to pour slowly to avoid the generation of bubbles.

[0013] Preferably, in step S7, the lithium salt includes one of lithium hexafluorophosphate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, fluorolithium sulfonyl imide, lithium bis(fluorosulfonyl)imide and lithium dioxalatoborate; and the anhydrous solvent is one of dichloromethane, N-methylpyrrolidone and tetrahydrofuran.

[0014] Preferably, in step S8, the method of pouring the uniform solution into the polytetrafluoroethylene mold is to pour slowly to avoid the generation of bubbles.

[0015] In a second aspect, the present application provides an ion-conductive elastomer that can self-repair and has high toughness, using the following technical solution: As a general technical concept, the present application also provides the above-mentioned self-repairable high-toughness ion-conductive elastomer, which is prepared by the preparation method of the above-mentioned self-repairable high-toughness ion-conductive elastomer.

[0016] By adopting the above technical solution, the obtained self-repairable and ultra-tough ion conductive elastomer does not contain any liquid components, thereby improving the stability of use; the obtained self-repairable and ultra-tough ion conductive elastomer has excellent mechanical properties, fast self-healing properties at room temperature and high ionic conductivity, which are currently at the leading level among ion conductive elastomers.

[0017] In summary, the beneficial technical effects of this application are: 1. Excellent mechanical properties: The ion conductive elastomer prepared by the strategy of soft and hard phase synergy has excellent mechanical properties. This means that the material can show good strength and toughness when subjected to external force and is not prone to fracture.

[0018] 2. Rapid self-healing performance at room temperature: The dynamic disulfide bonds and hexavalent hydrogen bonds in the elastomer can be broken and reorganized at room temperature, allowing the elastomer to self-repair after being damaged, thereby improving the durability and service life of the material.

[0019] 3. High ionic conductivity: through loose Li +The -O coordinated soft phase enables fast and uniform lithium ion transport, giving the material high ionic conductivity, which is of great significance for the application of ion-conductive elastomers in energy storage devices such as batteries and supercapacitors.

[0020] 4. No liquid component: The preparation method of the present application makes the obtained self-repairing ultra-tough ion conductive elastomer free of any liquid component, which improves the stability of use. This means that the material will not leak during use, which improves the safety of use.

[0021] 5. Simple preparation process: The preparation process of the present invention is simple, the materials are easily available, the cost is low, the reaction conditions are mild, no impurities are generated, and the yield is high. This makes the material suitable for commercial production and has high economic benefits.

[0022] 6. Environmentally friendly: The present invention is environmentally friendly and meets the application requirements in multiple fields. This means that the material has little impact on the environment during production and use, and meets the requirements of sustainable development.

[0023] In summary, the beneficial technical effects of the present application are mainly reflected in improving the mechanical properties, self-healing ability, ionic conductivity and stability of use of the material. At the same time, it has the advantages of simple preparation process, low cost and environmental friendliness, and has high commercial application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following is a brief introduction to the drawings used in the embodiments: Figure 1 The stainless steel-stainless steel button cell assembled from the ion conductive elastomer prepared in Examples 1 to 4 of the present application is 0.1-10 5 Electrochemical impedance spectroscopy at Hz; Figure 2 The stress-strain curves of the ion-conductive elastomers prepared in Examples 1 to 4 of the present application obtained by uniaxial stretching; Figure 3 A toughness diagram obtained by integrating the stress-strain curves of the ion-conductive elastomers prepared in Examples 1 to 4 of the present application; Figure 4 This is a diagram showing the self-healing performance of the ion conductive elastomer prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0025] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0026] Example 1 Step 1, taking 0.6 g of 4,4'-dicyclohexylmethane diisocyanate and drying it in a vacuum oven at 100°C to remove water for 12 hours; Step 2, add 2g of polytetrahydrofuran diol monomer into a Schlenk flask, stir the monomer at 120°C, cycle through vacuuming and filling with protective gas 3 times, then keep the vacuuming state for 2h, cool to 65°C, and finally fill with protective gas; Step 3, dissolving the 4,4'-dicyclohexylmethane diisocyanate treated in step 1 in 6 g of N,N-dimethylformamide, adding the polytetrahydrofuran diol monomer dried in step 2 after ultrasonic dissolution for 30 min, and then adding 30 μL of the catalyst diisobutyltin dilaurate, stirring and reacting at 65° C. for 1.5 h; Step 4, dissolve 0.25 mmol of 4,4'-diaminodiphenyl disulfide and 0.75 mmol of succinic acid dihydrazide in 8 mL of anhydrous N,N-dimethylformamide, and perform ultrasonication until completely dissolved to form a light yellow transparent solution; Step 5, further cooling the prepolymer product in step 3 to 40° C., then adding the chain extender solution in step 4, and stirring the reaction for 12 hours; Step 6, slowly pouring the reaction product of step 5 into a polytetrafluoroethylene mold, and removing a large amount of solvent in a 60° C. forced air oven for 12 hours, and then transferring to a 60° C. vacuum oven to remove residual solvent, to obtain a self-repairing, high-toughness elastomer; Step 7, dissolve 2 g of the elastomer of step 6 and 600 mg of dried lithium bis(trifluoromethylsulfonyl)imide in 20 mL of anhydrous solvent tetrahydrofuran, and stir for 12 h to obtain a light yellow uniform solution; Step 8: slowly pour the reaction product of step 7 into a polytetrafluoroethylene mold, remove a large amount of solvent in a 60°C forced air oven for 12 hours, and then transfer to a 60°C vacuum oven to remove residual solvent to obtain a self-repairing, high-toughness ion conductive elastomer.

[0027] Example 2 Step 1, taking 0.6 g of 4,4'-dicyclohexylmethane diisocyanate and drying it in a vacuum oven at 100°C to remove water for 12 hours; Step 2, add 2 g of polypropylene glycol monomer into a Schlenk flask, stir the monomer at 120° C., cycle through vacuuming and filling with protective gas 4 times, then maintain the vacuum state for at least 2 hours, cool to 65° C., and finally fill with protective gas; Step 3, dissolving the 4,4'-dicyclohexylmethane diisocyanate treated in step 1 in 6 g of N,N-dimethylformamide, adding the polytetrahydrofuran diol monomer dried in step 2 after ultrasonic dissolution for 30 min, and then adding 30 μL of the catalyst diisobutyltin dilaurate, stirring and reacting at 65° C. for 2 h; Step 4, dissolve 0.25 mmol of 4,4'-diaminodiphenyl disulfide and 0.75 mmol of succinic acid dihydrazide in 8 mL of anhydrous N,N-dimethylformamide, and perform ultrasonication until completely dissolved to form a light yellow transparent solution; Step 5, further cooling the prepolymer product in step 3 to 40° C., then adding the chain extender solution in step 4, and stirring the reaction for 12 hours; Step 6, slowly pouring the reaction product of step 5 into a polytetrafluoroethylene mold, and removing a large amount of solvent in a 60° C. forced air oven for 15 hours, and then transferring to a 60° C. vacuum oven to remove residual solvent, to obtain a self-repairing, high-toughness elastomer; Step 7, dissolve 2 g of the elastomer of step 6 and 600 mg of dried lithium bis(trifluoromethylsulfonyl)imide in 20 mL of anhydrous solvent tetrahydrofuran, and stir for 12 h to obtain a light yellow uniform solution; Step 8: slowly pour the reaction product of step 7 into a polytetrafluoroethylene mold, remove a large amount of solvent in a 60°C forced air oven for 13 hours, and then transfer to a 60°C vacuum oven to remove residual solvent to obtain a self-repairing, high-toughness ion conductive elastomer.

[0028] Example 3 Step 1, take 0.6 g of isophorone diisocyanate and dry it in a vacuum oven at 100° C. to remove water for 12 hours; Step 2, add 2g of polytetrahydrofuran diol monomer into a Schlenk flask, stir the monomer at 120°C, cycle through vacuuming and filling with protective gas 3 times, then keep the vacuuming state for 3h, cool to 65°C, and finally fill with protective gas; Step 3, dissolving the 4,4'-dicyclohexylmethane diisocyanate treated in step 1 in 6 g of N,N-dimethylformamide, adding the polytetrahydrofuran diol monomer dried in step 2 after ultrasonic dissolution for 30 min, and then adding 30 μL of the catalyst diisobutyltin dilaurate, stirring and reacting at 65° C. for 2 h; Step 4, dissolve 0.25 mmol of 4,4'-diaminodiphenyl disulfide and 0.75 mmol of succinic acid dihydrazide in 8 mL of anhydrous N,N-dimethylformamide, and perform ultrasonication until completely dissolved to form a light yellow transparent solution; Step 5, further cooling the prepolymer product in step 3 to 40° C., then adding the chain extender solution in step 4, and stirring the reaction for 12 hours; Step 6, slowly pouring the reaction product of step 5 into a polytetrafluoroethylene mold, and removing a large amount of solvent in a 60° C. forced air oven for 13 hours, and then transferring to a 60° C. vacuum oven to remove residual solvent, to obtain a self-repairing, high-toughness elastomer; Step 7, dissolve 2 g of the elastomer of step 6 and 600 mg of dried lithium bis(trifluoromethylsulfonyl)imide in 20 mL of anhydrous solvent tetrahydrofuran, and stir for 12 h to obtain a light yellow uniform solution; Step 8: slowly pour the reaction product of step 7 into a polytetrafluoroethylene mold, remove a large amount of solvent in a 60°C forced air oven for 14 hours, and then transfer to a 60°C vacuum oven to remove residual solvent to obtain a self-repairing, high-toughness ion conductive elastomer.

[0029] Embodiment 4: Step 1, taking 0.6 g of 4,4'-dicyclohexylmethane diisocyanate and drying it in a vacuum oven at 100°C to remove water for 12 hours; Step 2, add 2g of polytetrahydrofuran diol monomer into a Schlenk flask, stir the monomer at 120°C, cycle through vacuuming and filling with protective gas 3 times, then keep the vacuuming state for 2h, cool to 65°C, and finally fill with protective gas; Step 3, dissolving the 4,4'-dicyclohexylmethane diisocyanate treated in step 1 in 6 g of N,N-dimethylformamide, adding the polytetrahydrofuran diol monomer dried in step 2 after ultrasonic dissolution for 30 min, and then adding 30 μL of the catalyst diisobutyltin dilaurate, stirring and reacting at 65° C. for 1.5 h; Step 4, dissolve 0.25 mmol of 4,4'-diaminodiphenyl disulfide and 0.75 mmol of succinic acid dihydrazide in 8 mL of anhydrous N,N-dimethylformamide, and perform ultrasonication until completely dissolved to form a light yellow transparent solution; Step 5, further cooling the prepolymer product in step 3 to 40° C., then adding the chain extender solution in step 4, and stirring the reaction for 12 hours; Step 6, slowly pouring the reaction product of step 5 into a polytetrafluoroethylene mold, and removing a large amount of solvent in a 60° C. forced air oven for 12 hours, and then transferring to a 60° C. vacuum oven to remove residual solvent, to obtain a self-repairing, high-toughness elastomer; Step 7: Dissolve 2 g of the elastomer prepared in step 6 and 600 mg of dry lithium perchlorate in 20 mL of anhydrous tetrahydrofuran and stir for 12 h to obtain a light yellow homogeneous solution; Step 8: slowly pour the reaction product of step 7 into a polytetrafluoroethylene mold, remove a large amount of solvent in a 60°C forced air oven for 12 hours, and then transfer to a 60°C vacuum oven to remove residual solvent to obtain a self-repairing, high-toughness ion conductive elastomer.

[0030] Application Example 1 Assemble the stainless steel-stainless steel button cell battery: Stainless steel is used as the positive and negative electrodes, and the ion conductive elastomer prepared in the above Examples 1 to 4 is sandwiched. A 2025 type battery shell is used to assemble a stainless steel-stainless steel button battery in the order of negative electrode shell, stainless steel sheet, ion conductive elastomer, stainless steel sheet, gasket, spring sheet, and positive electrode shell.

[0031] The electrochemical impedance spectroscopy test of the assembled stainless steel sheet-stainless steel sheet symmetrical button cell was carried out on an electrochemical workstation with a frequency range of 0.1 Hz-10 5 Hz. The test was carried out on Chenhua CHI660E at a temperature of 30°C. The ionic conductivity of the elastomer was further calculated as σ = L / RS (L is the thickness of the sample, S is the contact area between the sample and the steel sheet, and R represents the intrinsic impedance of the sample obtained through testing); Various performance tests were conducted on the self-healing, high-toughness ion-conductive elastomers prepared in Examples 1 to 4. The results showed that they had the following significant characteristics: (1) good ionic conductivity: about 10 mS / m at 30°C; (2) high mechanical strength: 13.2 to 64.8 MPa measured by uniaxial stretching; (3) high elongation at break: 1130 to 1420% measured by uniaxial stretching; (4) high toughness: 55.21 to 250.81 MJm measured by uniaxial stretching; -3 ; (5) Excellent self-healing performance: It can self-heal to 100% at room temperature; (6) Good recyclability: It can be dissolved in anhydrous solvents and dried into a film and can be recycled multiple times.

[0032] Example 1 is a preferred embodiment of the present application, and its performance tests are as follows: (1) Good ionic conductivity: about 2.15 mS / m at 30°C; (2) High mechanical strength: 64.8 MPa measured by uniaxial stretching; (3) High elongation at break: 1130% measured by uniaxial stretching; (4) High toughness: 250.8 MJm measured by uniaxial stretching -3; (5) Excellent self-healing performance: It can self-heal to 100% at room temperature; (6) Good recyclability: It can be dissolved in anhydrous solvents and dried into a film and can be recycled multiple times.

[0033] See also Figure 1 As shown, Figure 1 The electrochemical impedance spectra of the ion conductive elastomers prepared in Examples 1 to 4 at 30°C are shown in Figure 1. Figure 1 It shows that the prepared ion conductive elastomer has good ionic conductivity (about 10mS / m).

[0034] See also Figure 2 As shown, Figure 2 The stress-strain curves of the dynamic supramolecular ion-conductive elastomers prepared in Examples 1 to 4 are shown in FIG. Figure 2 It is shown that the prepared ion conductive elastomer has ultra-high mechanical strength (13.2-64.8 MPa) and ultra-high elongation at break (1130-1420%).

[0035] See also Figure 3 As shown, Figure 3 The stress-strain curves of the dynamic supramolecular ion-conductive elastomers prepared in Examples 1 to 4 are integrated. Figure 3 It shows that the prepared ion conductive elastomer has ultra-high toughness (62.4~250.8MJm -3 ).

[0036] See also Figure 4 , Figure 4 The self-healing performance of the ion conductive elastomer prepared in Example 1 was tested. The results showed that the material could quickly recover to its original state at room temperature after being fractured, which significantly extended the service life of the material and reduced the cost.

[0037] It is noteworthy that the ion conductive elastomer prepared by the method of the present application does not contain any liquid components, thereby improving the safety and stability of its use.

[0038] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a self-repairing high-toughness ion-conductive elastomer, characterized in that: The following steps are involved: S1. Take the diisocyanate monomer and dry it in a vacuum oven at 60-100°C to remove water for at least 12 hours; S2, adding polyether diol monomer into the bottle, stirring the polyether diol monomer at 80-120° C., cyclically evacuating and filling with protective gas for at least 3 times, then maintaining the evacuation state for at least 2 hours, cooling to 60-70° C., and finally filling with protective gas; wherein the protective gas used is nitrogen or other inert gas; S3, dissolving the diisocyanate monomer treated in step S1 in an anhydrous solvent with a mass ratio of 1:10 to 10:1 at a molar ratio of diisocyanate monomer to polyether diol monomer of 2:1, adding the polyether diol monomer dried in step S2 after ultrasonic dissolution for at least 30 minutes, and then adding 10 to 30 μL of a catalyst, stirring and reacting at 60 to 80° C. for at least 30 minutes to obtain a prepolymer product; S4, dissolving a chain extender containing a reversible bond in an anhydrous solvent with a mass ratio of 1:10 to 10:1 to obtain a chain extender solution, wherein the anhydrous solvent is the same as the anhydrous solvent in step S3; S5, further cooling the prepolymer product in step S3 to 30-60°C, then adding the chain extender solution, and stirring the reaction for at least 12 hours; S6, pouring the reaction product in step S5 into a polytetrafluoroethylene mold, and removing a large amount of solvent at 60-70° C. for at least 12 hours, and then transferring to a vacuum oven at 60-70° C. to remove residual solvent, to obtain a self-repairing high-toughness elastomer; S7, dissolving the self-healing high-toughness elastomer in step S6 and 10-40% by mass of dry lithium salt in an anhydrous solvent with a mass ratio of 1:10 to 10:1, and stirring for at least 12 hours to obtain a uniform solution; S8. Cast the uniform solution in step S7 into a polytetrafluoroethylene mold, remove a large amount of solvent at 60-70°C for at least 12 hours, and then transfer to a vacuum oven at 60-70°C to remove residual solvent to obtain a self-repairable and highly tough ion conductive elastomer.

2. The method for preparing a self-repairing high-toughness ion-conductive elastomer according to claim 1, characterized in that: In step S1 , the diisocyanate monomer includes one or more of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, butyl diisocyanate, alicyclic diisocyanate and 4,4′-dicyclohexylmethane diisocyanate.

3. The method for preparing a self-repairing high-toughness ion-conductive elastomer according to claim 1, characterized in that: In step S2, the polyether diol monomer includes one or more of polypropylene glycol, polyethylene glycol, polytetramethylene glycol, polycaprolactone glycol and polytrimethylpropylene glycol.

4. The method for preparing a self-repairing high-toughness ion-conductive elastomer according to claim 1, characterized in that: In step S3, the anhydrous solvent includes one of N,N-dimethylformamide and N,N-dimethylacetamide; and the catalyst is one of diisobutyltin dilaurate and triethanolamine.

5. The method for preparing a self-repairing high-toughness ion-conductive elastomer according to claim 1, characterized in that: In step S4, the chain extender is composed of 4,4'-diaminodiphenyl disulfide and succinic acid dihydrazide in a molar ratio of 10:1 to 1:

10.

6. The method for preparing a self-repairing high-toughness ion-conductive elastomer according to claim 1, characterized in that: In step S5, the chain extender solution is added dropwise and slowly using a constant pressure separatory funnel.

7. The method for preparing a self-repairing high-toughness ion-conductive elastomer according to claim 1, characterized in that: In step S6, the reaction product is poured into the polytetrafluoroethylene mold by slowly pouring to avoid the generation of bubbles.

8. The method for preparing a self-repairing high-toughness ion-conductive elastomer according to claim 1, characterized in that: In step S7, the lithium salt includes one of lithium hexafluorophosphate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium fluorosulfonyl imide, lithium bis(fluorosulfonyl)imide and lithium dioxalatoborate; and the anhydrous solvent is one of dichloromethane, N-methylpyrrolidone and tetrahydrofuran.

9. The method for preparing a self-repairing high-toughness ion-conductive elastomer according to claim 1, characterized in that: In step S8, the method of pouring the uniform solution into the polytetrafluoroethylene mold is to pour slowly to avoid the generation of bubbles.

10. An ion-conductive elastomer with high toughness and self-repairability, characterized in that: The ion conductive elastomer is prepared by the method for preparing a self-repairable and high-toughness ion conductive elastomer as described in any one of claims 1 to 9.